Ethical Dimensions of User Centric Regulation - Lachlan Urquhart (ORBIT Journal, 2017)
In this paper, we question the role of information technology (IT) designers in IT regulation. Through our concept of user centric regulation (UCR) we unpack what a closer alignment of IT design and regulation could mean. We also situate how they can respond to their ethical and legal duties to end users. Our concept asserts that human computer interaction (HCI) designers are now regulators and as designers are not traditionally involved in the practice of regulation hence the nature of their role is ill-defined. We believe designers need support in understanding what their new role entails, particularly managing ethical dimensions that go beyond law and compliance. We use conceptual analysis to consolidate perspectives from across Human Computer Interaction and Information Technology Law and Regulation, Computer Ethics, Philosophy of Technology, and beyond. We focus in this paper on the importance of mediation and responsibility and illustrate our argument by drawing on the emerging technological setting of smart cities.